Comparison of the Continuous and Intermittent Relaxation Test - Sleger, Vladimir; Mizera, Cestmir (Manufacturing Technology Journal, 2015)
The article presents the measurement results of the relaxation of long-term loaded compression springs manufactured out of non-alloy steel. The goal was to determine the differences between the interrupted and uninterrupted tests. During the relaxation test that lasted 5000 hr in a laboratory with a temperature of 22ºC, initial shear stress set at a value of 30% of the ultimate tensile strength of the material, decreased the strength of the springs with a wire diameter of 1 mm by 3.6%, springs with a wire diameter of 3.15 mm by 2.5%, and springs with a wire diameter of 5 mm by 1.3%. The difference in the results was found in tests 16 times and 4 times interrupted to measure the current relaxation. The results of intermittent tests cannot be considered as relaxation values for statically loaded springs. Conversely, when determining the maximum tension of quasi-statically loaded springs with respect to the relaxation, the uninterrupted relaxation tests cannot be used.
Keywords: Compression springs; Patented wire; Long-term test; Room temperature; Static loading